2021
DOI: 10.11646/phytotaxa.478.1.10
|View full text |Cite
|
Sign up to set email alerts
|

<p align="left"><strong>A new species with pink lamellae of Amanita section <em>Caesareae</em> from China</strong></p>

Abstract: Amanita fense is described and illustrated as a new species from China based on morphological and molecular evidence. This fungus is mainly distributed in the eastern, northeastern and southwestern regions of China, such as Anhui, Liaoning, and Yunnan. It is characterized by medium-sized basidiomata, a buff to cacao brown pileus with long-striate pileus margin, pinkish lamellae, and ellipsoid to elongate inamyloid spores. This is the fifth taxon with pink lamellae within Amanita section Caesareae. We provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A phylogenetic tree obtained from the ML analysis is represented in Figure 2 . Our phylogenetic tree was constructed with the aim of having similar outcomes to previous phylogenetic studies [ 4 , 52 , 53 , 54 ]. The phylogenetic tree consisted of 62 specimens of Amanita sect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A phylogenetic tree obtained from the ML analysis is represented in Figure 2 . Our phylogenetic tree was constructed with the aim of having similar outcomes to previous phylogenetic studies [ 4 , 52 , 53 , 54 ]. The phylogenetic tree consisted of 62 specimens of Amanita sect.…”
Section: Resultsmentioning
confidence: 99%
“…The current classification of the genus Amanita is based on combined data on their morphological characteristics and molecular data. Moreover, multi-gene molecular phylogeny has provided researchers with a powerful tool for the identification of the Amanita species [ 4 , 14 , 36 , 52 , 53 , 54 , 58 ]. In this present study, specimens of the edible Amanita species collected in northern Thailand were identified as A. hemibapha, A. pseudoprinceps, A. rubromarginata, and A. subhemibapha based on morphological characteristics and multi-gene phylogenetic analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have identified 27 taxa, comprising 23 species, 2 varieties, and 2 forms, in China ( Cui et al., 2018 ; Su et al., 2022 ). Previous studies have reported 21 species of section Caesareae ( Cui et al., 2018 ; Mu et al., 2021 ). The species belonging to section Validae were characterized by a pileal margin non-striae and non-appendiculate; annulus membranous, dominance of filamentous hyphae; volval remnants often as verrucae, warts, flocci, patches, or occasionally as short limb; amyloid basidiospores; and absence of clamps.…”
Section: Discussionmentioning
confidence: 99%
“…A. brunneola can be distinguished from A. fense and A. longistriata on the basis of its longer striations (0.3-0.5 R) on the pileal margin, white to cream lamellae, and a white stipe. Basidiospores of A. brunneola (10.0-13.0 × 8.0-11.0 mm) are longer than those of A. longistriata, whereas they are shorter than those of A. fense (Imai, 1938;Gilbert, 1940;Gilbert, 1941;Hongo, 1959;Yang and Doi, 1999;Yang, 2005;Yang, 2015;Cui et al, 2018;Wu et al, 2021).…”
Section: 21mentioning
confidence: 99%